A new exponentiated class of distributions: Properties and applications. Issue 12 (18th June 2017) - Rezaei, S.; Marvasty, A. K.; Nadarajah, S.; Alizadeh, M.
ABSTRACT: Motivated by series-parallel-series systems, we introduce a new generator of continuous distributions with three extra parameters called the generalized exponentiated class of distributions . We study its mathematical properties and introduce a bivariate extension of the class. We discuss the estimation of its parameters by maximum likelihood and illustrate the potentiality of the class by applications to two real datasets.